The legal basis of the request in administrative litigation (a comparative analytical study) - QADIR, SUZAN OTHMAN; SALIH, AHMED KALAK (Journal of Legal and Political Studies, 2024)
The application submitted to the administrative judiciary is one of the most important legal guarantees for litigants before the administrative judiciary, in addition to its role in protecting public rights and freedoms in the state. Rather, it represents the positive aspect of the legal state, as violating this procedural right constitutes a legal presumption of the dictatorship of the ruling authority. Thus, we see many international treaties related to human rights and public freedoms concerned with this matter, and this is also the reason why many constitutions focus on the principle of the right to litigation and equality before the law. As the administrative judge, when considering the subject of the administrative dispute and during the course of the administrative dispute, is bound by the content of the application submitted to him, considering that it represents the legal framework for his legal activity, as the submission of the application results in the utmost importance for the judiciary, as the submission of the application transforms the dispute between the administrative authority and the private law persons into an administrative dispute, as the application begins the dispute, which requires the judiciary to focus on it until it decides the dispute, whether by a decisive ruling on the subject, or by abandonment, or by lapse, or by delivery, or by agreement and reconciliation. Therefore, the research shed light on the concept of the request and all the foundations on which the judicial request is built, and at the end the researchers put forward proposals, the most important of which is the proposal for the draft law on administrative litigation, in addition to the necessity of organizing the request in a way that allows the applicant to submit it in writing or electronically, as the French legislator did, without being satisfied with general texts. Keywords: Law, Request in Administrative Litigation, Litigation Law
Keywords: Law; Request in Administrative Litigation; Litigation Law